Some Attention Using VTS and Its Relationship with Air Rifle Shooting Accuracy - Khalid, thikra (Journal of Physical Education, 2019)
The importance of the research lies in coaches interest in attention to develop shooting accuracy and improving the shooters' level through performance assessment and development using special physical exercises. The problem of the research lies in the differences among female shooters in shooting due to their differences in response to training. Most coaches don’t use scientific evaluation to analyze performance and identifying the weaknesses and strength in female shooters. The aim of the researcher is to identify the relationship between size, concentration, and attention with the accuracy in air rifle shooting. The researcher used the descriptive method. The data was collected and treated using proper statistical operations to come up with the results. The researcher concluded that attention has a positive relationship with shooting accuracy in young female air rifle shooters. Finally she recommended stressing on the importance of attention during shooters' selection.